Network Model of the CPE - Valsa, Juraj; Dvorak, Petr; Friedl, Martin (Společnost pro radioelektronické inženýrství, 2011)
Analysis of fractal systems (i.e. systems described by fractional differential equations) necessitates to create an electrical analog model of a crucial subsystem called Constant Phase Element (CPE). The paper describes a possible realization of such a model, that is quite simple and in spite of its simplicity makes it possible to simulate the properties of ideal CPEs. The paper also deals with the effect of component tolerances on the resultant responses of the model and describes several typical model applications.
Keywords: Fractional differential equations; Constant Phase Element; Warburg impedance